Light force manipulation of gallium atoms - Rehse, Steven James, author; Lee, Siu Au, advisor; Menoni, Carmen, committee member; Lundeen, Stephen, committee member; Sites, James, committee member (Colorado State University. Libraries, 2002)
We have demonstrated the first one-dimensional laser cooling of neutral gallium atoms. We identified the 4p2P3/2(F=3) → 4d2D5/2(F=4) transition at 294.45 nm as a cycling transition suitable for laser cooling. We developed a frequency stabilized tunable UV laser capable of generating over 90 mW for use at that wavelength. A careful spectroscopy of the hyperfine structure was performed on the 294.45 nm transition. This spectroscopy significantly improved the measurement of the Ga hyperfine constants and corrected existing errors in the literature.

Using the UV laser, a beam of Ga atoms was cooled in one-dimension utilizing the polarization gradient technique. With a cooling laser detuned by at least -14 MHz from the 4p2P3/2(F=3) → 4d2D5/2(F=4) transition and a power of at least 60 mW (I/I0 ≅ 12) the transverse velocity of the atoms was reduced to <14 cm/s, which corresponds to a temperature of <165 pμ. This is roughly one-half the Doppler cooling limit. Sub-Doppler cooling due to the polarization gradient was directly observed and the cooling efficiency as a function of cooling laser interaction length and power was investigated.

Optical pumping of atoms out of the F=3 state due to the UV laser was observed during cooling. Optical repumping with a second weaker UV laser beam was investigated. A frequency shifted beam derived from the cooling beam was used for repumping and the populations of the hyperfine levels in the 4p2P3/2 state were measured with a 417 nm probe laser. Two different frequency shifts for the repump beam were investigated: +334 MHz and +410 MHz. Both were found to repopulate the F=3 state, although they redistributed the atoms among the other hyperfine states in different ways.

Light force focusing of the cooled Ga atomic beam was attempted on the 4p2P3/2(F=3) → 5s2SI/2(F=2) transition at 417.32 nm using 11 mW of laser light detuned 200 to 400 MHz from resonance. Self-organized islanding of the Ga atoms during deposition on silicon, gallium arsenide, and fused silica substrates precluded any observation of the light force focusing.
Keywords: atomic physics